Effect of sulfur annealing on the morphological, structural, optical and electrical properties of iron pyrite thin films formed from FeS2 nano-powder - Thanh Kieu Trinh (Springer US, 2023)
Iron pyrite (FeS2) thin films were fabricated by spin coating the solution of FeS2 nanocrystals of ~40 nm in size on glass substrates, followed by annealing in a sulfur environment at different temperatures. The effect of sulfurization temperature on the morphology, structural, optical and electrical properties was investigated. With increase of the sulfurization temperature, the grain size and crystallinity of the films was improved, although some cracks and voids were observed on the surface of thin films. The band gap of the FeS2 films was decreased at higher sulfurization temperature. The electrical properties were also changed, including the increasing in resistivity and the decrease in Hall mobility, with increase of sulfurization temperature. The change in the optical and electrical properties of the FeS2 thin films was explained based on the changes of phase, morphology, surface, and grain boundary property.